Creativity Training Guide to Exercises and Techniques for Unleashing Your Creative Process to come up with Uniques Ideas and to Turn Those Ideas into Reality - Mitch, Jensen (‎Independently published, 2020)
Knowing how to work on your creative capabilities is necessary in order to solve difficult problems and come up with creative solutions. Showing you what you can do to start training your creativity muscle today is what this book is all about.